The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/hrp.0000000000000246
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Paid Maternity Leave on the Mental and Physical Health of Mothers and Children: A Review of the Literature and Policy Implications

Abstract: For decades, national paid maternity leave policies of 12 weeks or more have been established in every industrialized country except the United States. Despite women representing 47% of the current U.S. labor force, only 16% of all employed American workers have access to paid parental leave through their workplace. As many as 23% of employed mothers return to work within ten days of giving birth, because of their inability to pay living expenses without income. We reviewed recent studies on the possible effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
105
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(120 citation statements)
references
References 40 publications
0
105
0
1
Order By: Relevance
“…Moreover, programs such as Listening Visits (a nondirective counseling intervention which originated in the United Kingdom) could be enacted in the United States to provide mothers with additional emotional support in the context of home visits [ 89 ]. Additionally, paid parental leave initiatives [ 88 , 90 , 91 ] take the onus off of mothers for balancing work and financial concerns with postpartum adjustment. Implementing similar initiatives in the United States would address critical gaps and could begin to cultivate an environment around mothers that predisposes to higher levels of postpartum function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, programs such as Listening Visits (a nondirective counseling intervention which originated in the United Kingdom) could be enacted in the United States to provide mothers with additional emotional support in the context of home visits [ 89 ]. Additionally, paid parental leave initiatives [ 88 , 90 , 91 ] take the onus off of mothers for balancing work and financial concerns with postpartum adjustment. Implementing similar initiatives in the United States would address critical gaps and could begin to cultivate an environment around mothers that predisposes to higher levels of postpartum function.…”
Section: Discussionmentioning
confidence: 99%
“…The total financing need of both our estimate for informal sector, and the other estimate from previous study on formal sector [30] shows that the combined financing need of providing MCT to eligible WRA in both the formal and informal sectors at 100% coverage based on minimum wage amount to be around US$2 billion per year, roughly 4.5 times lower than the estimate of the cost of not breastfeeding in Indonesia. This indicates the value of investing in MCT, in addition to its benefits in terms of alleviating the costs of sickness, cognitive losses and deaths due to not breastfeeding and improve maternal-child physical and mental health and family wellbeing, and also to potentially increase women's participation in the labour market [4][5][6]8,11,12,[14][15][16]66]. However, the proposed MCT approach would require, among other things, sound monitoring to ensure that breastfeeding actually took place, consistency in the best timing of delivery of cash distribution and breastfeeding counselling visits, recognizing that many mothers receiving the cash transfer face major social determinants of health challenges.…”
Section: Resultsmentioning
confidence: 99%
“…Such benefits include alleviating the costs of sickness, cognitive losses and deaths due to not breastfeeding [4][5][6]14]. Providing paid maternity leave entitlement for working women may also be useful to improve maternal-child physical and mental health and family wellbeing, and also to potentially increase women's participation in the labour market [8,11,12,15,16]. Studies have indeed shown that paid maternity leave may improve breastfeeding outcomes; mothers receiving paid leave for more time, breastfeed longer [9,11,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The total cost of both our estimate for informal sector, and the other estimate from previous study on formal sector [30] shows that the combined cost of providing MCT to eligible WRA in both the formal and informal sectors at 100% coverage based on minimum wage amount to be around US$2 billion per year, roughly 4.5 times lower than the estimate of the cost of not breastfeeding in Indonesia. This indicates the value of investing in MCT, in addition to its benefits in terms of alleviating the costs of sickness, cognitive losses and deaths due to not breastfeeding and improve maternal-child physical and mental health and family wellbeing, and also to potentially increase women's participation in the labour market [4][5][6]8,11,12,[14][15][16]67]. However, the proposed MCT approach would require, among other things, sound monitoring to ensure that breastfeeding actually took place, consistency in the best timing of delivery of cash distribution and breastfeeding counselling visits, recognizing that many mothers receiving the cash transfer face major social determinants of health challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Such benefits include alleviating the costs of sickness, cognitive losses and deaths due to not breastfeeding [4][5][6]14]. Providing paid maternity leave entitlement for working women may also be useful to improve maternal-child physical and mental health and family wellbeing, and also to potentially increase women's participation in the labour market [8,11,12,15,16]. Studies have indeed shown that paid maternity leave may improve breastfeeding outcomes; mothers receiving paid leave for more time, breastfeeding longer [9,11,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%